Customer perceptions towards Islamic financing : An comparative studies between Islamic finance and conventional loans - Navanithan, Sachithanandam (2014)
The expansion of Islamic banking industry the financial markets of the world has made this newly born industry a ground reality. Islamic banking industry have shown the current global financial crisis in entire market. Islamic banking is a new phenomenon that has taken many observers by surprise. The speed with Islamic banks have sprung up and the rate at which they have progressed make it worthwhile to study them systematically. The purpose of this paper is to examine the main factors that motivate customers to deal with Islamic banks particularly in a dual banking environment. A discussion on factors relating to how Shariah complaints and Islamic value initiatives as part of potential customers' banking selection criteria is also included. Islamic Banking and Finance (IBF) involves wider ethical and moral issues than simply 'interest-free' transactions. Its advocates argue that these make it more economically efficient than conventional banking and promote greater economic equity and justice. To what extent. then, do actual Islamic Banking practices live up to the ideal, and how different are they from conventional banking? A preliminary investigation shows that, three decades after its introduction, there remain substantial divergences between IBF's ideals and its practices, and much of IBF still remains functionally indistinguishable from conventional banking. This runs counter to claims by IBF advocates that it would rapidly differentiate itself from conventional banking. However, despite not providing an alternative to conventional banking and finance. IBF does strengthen a distinctly Islamic identity by providing the appropriate Islamic terminology for the factor of conventional financial transactions.